Notary Malpractice in Carrying Out Their Duties and Authorities - Winanto Wiryomartani (Global Legal Review, 2021)
As an official whose duty and authority is making authentic deeds, a Notary is responsible for all the content of the deed he/ she made and all the information relating to the deed made before/ by him/ her, based on the Official Oath of the Notary and Notary Law. Notary is a noble position (noblese obligue), and Notaries are expected to keep their dignity as official. The consequences of such honorable position and authority of Notary is that Notaries are obliged to do everything that is regulated in the Notary Law and obey everything that is prohibited by the law, regulations, and the Notary’s Code of Ethics, in carrying out both their duties and authority, Notaries are responsible for any consequences arises from any violation of the position of a Notary. For any malpractice committed by a Notary, a Notary may be held liable to civil and criminal lawsuits. This article explains about: (1) The law and regulations applied to Notary in Indonesia in carrying out their duties and authorities. (2) How does the Notary practice in Indonesia in carrying out their duties and authorities. (3) How the ideal Law and Regulations should be applied to Notary, so that Notary malpractice can be eliminated, or at least reduced, and Notaries can carry out their duties and authorities as they are mandated.